2022
DOI: 10.3390/su142315810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Wind Speed on Efficiency of Five Photovoltaic Module Technologies for Different Climatic Zones

Abstract: The objective of this study is to investigate the effect of temperature and wind speed on the performance of five photovoltaic (PV) module technologies for different climatic zones of Pakistan. The PV module technologies selected were mono-crystalline silicon (MC); poly-crystalline silicon (PC); heterogeneous intrinsic thin-film (TFH); copper–indium–allium–selenide (TFC); and thin-film amorphous silicon (TFA). The module temperature and actual efficiency were calculated using measured data for one year. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Second, a more accurate estimate for operating temperature of PV panels in the field can be calculated using the relationship [53] 𝑇…”
Section: Modeling Photovoltaic Array Performancementioning
confidence: 99%
“…Second, a more accurate estimate for operating temperature of PV panels in the field can be calculated using the relationship [53] 𝑇…”
Section: Modeling Photovoltaic Array Performancementioning
confidence: 99%
“…The conversion efficiency, η PV_String , can be defined as the ratio of the output power of the PV string to the received solar irradiance, which can be used to evaluate the operating state of the PV string, and it can be defined as [3]:…”
Section: Distribution Characteristics Of Conversion Efficiencymentioning
confidence: 99%
“…Currently, most PV system performance evaluation methods use specific evaluation indicators. Tahir et al analyzed the variation in the conversion efficiency of photovoltaic modules of five technological routes under different environmental conditions [3]. Al-Ghussain et al analyzed the accuracy of four PV module operating temperature calculation models considering wind speed based on the results of annual power generation and analyzed the effect of the cleaning frequency on annual power generation and the Levelized Cost of Energy (LCOE) [4].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the module's surface temperature decreased on average by 11 °C, 16 °C, and 21 °C at a wind speed of 1 m/s, 2 m/s, and 5 m/s at an illumination of 400 W/m 2 . Tahir et al [11] examined the Impact of wind speed and temperature on five types of PV panels for various regions in Pakistan. The obtained results observed a decrease in PV efficiency when considering only the effect of temperature.…”
Section: Introductionmentioning
confidence: 99%